Improving the safety climate in hospitals by a vignette-based analysis of adverse events: a cluster randomised study. (18th June 2018) - Occelli, Pauline; Quenon, Jean-Luc; Kret, Marion; Domecq, Sandrine; Denis, Angélique; Delaperche, Florence; Claverie, Olivier; Castets-Fontaine, Benjamin; Amalberti, René; Auroy, Yves; Parneix, Pierre; Michel, Philippe
Abstract: Objective: To assess the impact of a vignette-based analysis of adverse events (AEs) on the safety climate (SC) of care units. Design: Prospective, open, cluster (a unit) randomised controlled trial. Setting: Eighteen acute care units of seven hospitals in France. Participants: Healthcare providers who worked in the units. Intervention: Vignette-based analyses of AEs were conducted with unit's providers once per month for six consecutive months. The AEs were real cases that occurred in other hospitals. The hospital risk manager conducted each analysis as follows: analysis of the immediate and root causes of the AE; assessment of the care unit's vulnerabilities and existing barriers in the occurrence of an identical AE and search for solutions. Main Outcome Measure: SC was measured using the French version of the Hospital Survey on Patient Safety Culture questionnaire. The primary outcome was the difference in the 'Organisational learning and continuous improvement' dimension score, from before to after the analyses. Results: Median participation rate in the analyses was 20% (range: 7–45%). Before intervention, the response rate to the SC survey was 80% ( n = 210) in the intervention group and 73% ( n = 191) in the control group. After intervention, it was 59% ( n = 141) and 63% ( n = 148), respectively. The dimension score evolved differently for the groups from before to after intervention (intervention: +10.2 points ±8.8; control: −3.0 points ±8.5, P = 0.04). Side effects were not measured. Conclusions: Vignette-based analysis was associated with the improvement of the perception of participants regarding their institution's capacity for organisational learning and continuous improvement.